The hepatoprotective and antioxidant effects of Momordica charantia methanolic extract against paracetamol induced hepatotoxicity in rats (مجلة البحوث الأكاديمية, 2018)
The fruits of Momordica charantia are commonly used in Asian countries for various medicinal purposes. In this study, the hepatoprotective and antioxidant effects of Momordica charantia fruits and leaves methanolic extracts were investigated in rats against paracetamol (PCM) induced liver injury. Pretreatment of rats with MCME of fruits and leaves parts (300 mg/kg for 7 days) significantly prevented the PCM (1500 mg/kg) induced hepatic damage as indicated by the decrease in  serum marker enzymes (AST, ALT, and ALP). Parallel to these changes, MCME treatments also prevented PCM-induced oxidative stress in the rats’ liver by restoring the levels of hepatic antioxidant enzymes (SOD, CAT, and GPx). Histologically, our results indicate that MCME of fruits and leaves conserved the hepatic tissue architecture and  prevented the hepatic injuries associated with PCM intoxication. In conclusion, the MCME of fruits and leaves proved to have hepatoprotective and antioxidant potentials and further studies should be performed to isolate the bioactive compounds in these extracts